GRANITIC MAGMA MIXING VERSUS BASALTIC MAGMA MIXING: NEW VIEWPOINTS ON GRANITIC MAGMA MIXING PROCESS: SOME CRUCIAL QUESTIONS ON GRANITE STUDY (1) - Zhang Q.; Jin W.J.; Pan G.Q.; Li C.D.; Jia X.Q. (My University, 2007)
How granitic magmas are mixed has become an interesting topic in recent years. Many workers are trying to interpret the variation of the composition of mixing granites with the different proportion of several end-members. However, we argue that such kind of mixing process for granites is uncommon and is unlikely happened in the field on the basis of a comparison of the properties of granite and basalt. The ability or competence that two granitic magmas can be mixed mainly depends on the viscosity and temperature of the magmas. The viscosity is related to the structure of SiO4 tetrahedron in the rocks. Granites in comparison with basalts have relatively high SiO2 contents and low temperature, and therefore granitic magmas have low competence to be mixed with each other. Unlike the mixing process of basaltic magmas, granitic magmas are more likely mingling, rather than mixing, with each other. There is rare example for the mixing of granitic magmas, the only case is high-Mg andesite or high-Mg adakite formed by mixing of adakite and upwelling mantle. Many workers argued that mafic microgranular enclaves (MME) in granites are the direct evidence for the mixing of granitic magmas. However, we argue that it is an exact evidence for that granitic magmas are difficult to be mixed with these mafic enclaves. Granitic rocks are actually heterogeneous in compositions because they have derived from heterogeneous sources with complicated melting processes. It is thus unlikely to assume the original granites are homogeneous. The variation of compositions of granites and the correlation of elements in Harker diagrams are mainly the results of heterogeneity of sources, rather than mixing or differentiation processes. Usually magmas tend to be homogeneous by mixing in magma conduits on the way upwelling to emplacement and at the same time they may become heterogeneous with the crustal contamination. However, grantic magmas are hard to be as homogeneous as basaltic magmas in this process because of their higher viscosity than that of basaltic magmas. Therefore, not only geochemical compositions of granites but also their physical properties should be considered in the study of the origin of granites, and it should be cautious when using geochemical data to discriminate the origin and tectonic environment of granites.